Analisis Strategi Optimalisasi Proses Produksi Untuk Maksimisasi Profit di Hisana Fried Chicken - Billy Steven Naldo Putra Hulu; Adriel Enda Hagana Tarigan; Nerli Cinthya Delvi Silaen; Ainun Mardhiyah (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the strategy of optimizing the production process at Hisana Fried Chicken in an effort to maximize profit. Through a qualitative approach, this study collected data from interviews with management and employees, as well as direct observation at the production site. The results of the study indicate that the application of modern technology, employee training, and efficient supply chain management are the keys to increasing productivity and profitability. This study also provides recommendations for companies to improve innovation and strategies that have been implemented.